Comparative Effects of Different Surface Treatments on Shear Bond Strength of Metal Brackets Bonded to Eroded Enamel: An in Vitro Study - Soleimani, Milad; Banaei , Hengameh; Mohammadian , Manijeh (Galen Medical Journal, 2025)
Background: This study aimed to compare the effects of different surface treatments on shear bond strength (SBS) of metal brackets to eroded enamel. Materials and Methods: In this in vitro study, 76 extracted premolars were immersed in Coca-Cola 4 times, each time for 2 minutes to cause enamel erosion. They were then randomly assigned to 4 groups (n=19) for surface treatment by acid etching (control), bur grinding plus acid etching, sandblasting plus acid etching, and erbium-doped yttrium aluminum garnet (Er:YAG) laser irradiation plus acid etching. Metal brackets were then bonded to the buccal surface of the teeth and after thermocycling, their SBS was measured in a universal testing machine. After debonding, the adhesive remnant index (ARI) score was determined under a stereomicroscope. SBS of higher than 6 was considered as optimal (Reynolds threshold). Results: The control group showed the highest, and the laser group showed the lowest SBS; however, the difference in SBS was not statistically significant among the four groups (P=0.35). Acid etching group had 2 cases of failure in SBS values, while other groups had none. The study groups had no significant difference in the ARI scores either (P=0.82); nonetheless, sandblasting and laser groups had the highest frequency of ARI score 3 (all adhesive remaining on the surface). Conclusion: Bur grinding, sandblasting, and Er:YAG laser irradiation did not significantly change the SBS of metal brackets to eroded enamel compared with acid etching alone, and all the tested methods yielded acceptable SBS values.